The development and testing of a training intervention designed to improve the acquisition and retention of CPR knowledge and skills in ambulance paramedics - Govender, Pregalathan (Division of Emergency Medicine, 2016)
Despite several therapeutic advances in cardio-pulmonary resuscitation (CPR), there has been little overall improvement in the out-of-hospital, cardiac arrest (OHCA) survival rates. Reports indicate that, although the incidence and outcome of OHCA vary across the globe, the median reported rates of survival at hospital discharge have remained below 10% for the 30 years preceding this study. One of the factors associated with this low survival rate is the deficient quality of the CPR provided during an OHCA by paramedics. Despite revised training standards, structured CPR training programmes and industry-regulated CPR refresher training schedules, paramedic-delivered CPR (pdCPR) during OHCAs is reported to be both inadequate and rarely in line with established resuscitation guidelines. International resuscitation bodies such as the International Liaison Committee on Resuscitation (ILCOR) postulate the need for tailored CPR training interventions in order to improve CPR performance. The aim of this study was to investigate the impact of a tailored pdCPR training intervention on pdCPR performance. The study was conducted in four phases and, using a mixed-method, multiphase design the study developed, implemented and evaluated the impact of a pdCPR training intervention which had been designed and tailored to improve the acquisition and retention of knowledge and skills by ambulance paramedics (AP). The primary outcome measure used in the study was the achievement of a competent rating which reflected the ability of the AP in question to perform high-quality, effective CPR as determined and evaluated by a 26 measure CPR Rapid Evaluation Tool predicated on variables derived from the globally accepted Cardiff list. Each of the 26 measures represented a treatment element within a pdCPR care bundle and which had been shown to contribute to successful resuscitation.